EL ACUSATIVO SG. LATINO DE TEMAS EN -S Y -SONANTE - Jiménez Zamudio, Rafael (Myrtia, 1987)
Opposed to the Monteil's idea considering the singular Latin accusative in - stems, -s- stems and -l, -r, -m, -n stems to be a remodelling form, the author of the present paper thinks they are to be reconstructed from *-eH2m.,*-sm., *-lm., *-mm., *-rm., *-nm..